Rabindranath Tagore in the 21st Century Theoretical Renewals - Banerji, Debashish; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2015)
This critical volume addresses the question of Rabindranath Tagore's relevance for postmodern and postcolonial discourse in the twenty-first century. The volume includes contributions by leading contemporary scholars on Tagore and analyses Tagore's literature, music, theatre, aesthetics, politics and art against contemporary theoretical developments in postcolonial literature and social theory. The authors take up themes as varied as the implications of Tagore’s educational vision for contemporary India; new theoretical interpretations of gender, queer elements, feminism and subalternism in Tagore's literary and social expressions; his language use as a vehicle for a dialogue between positivism, Orientalism and other constructs in the ongoing process of globalization; the nature of the influence of Tagore's music and literature on national and cultural identity formation, particularly in Bengal and Bangladesh; and intersubjectivity and critical modernity in Tagore’s art. This volume opens up a space for Tagore’s critique and his creative innovations in present theoretical engagements.
Chapter 1. Introduction: Theory and the Performative Politics of Punctuation -- Chapter 2. The Rustle of Language -- Chapter 3. Translating Tagore: Shifting Paradigms -- Chapter 4. Two Giant Brothers -- Chapter 5. Tagore’s Idea of “World Literature” -- Chapter 6. Rethinking Cosmopolitan Modernity: Rabindranath Tagore on Nationalism and Internationalism -- Chapter 7. The Bauhaus, Rabindranath Tagore and his Paintings -- Chapter 8. Why Ratan fell in Love Unnoticed and Why Ashu was Ashamed: Tagore’s Short Fiction and the Ethics of Feeling -- Chapter 9. Remembering Robi: Childhood, Freedom and Rabindranath Tagore -- Chapter 10. The Educational Efforts of Rabindranath Tagore -- Chapter 11. The Delineation of the Female Subject in Rabindranath Tagore’s Novel Farewell, My Friend -- Chapter 12. Gender, Nation, and the Vicissitudes of Kalpana: Choreographing Womanly Beauty in Tagore’s Dance Dramas -- Chapter 13. Chitrangada and Contemporary Queer Appropriations of Tagore -- Chapter 14. Tagore and the North-East: Dialectics of Human Intellection and the Nature of Aesthetic Reflection -- Chapter 15. Rabindrasangeet and Modern Bengali Subjectivity -- Chapter 16. Tagore and National Identity Formation in Bangladesh -- Chapter 17. Tagore Through Portraits: An Intersubjective Picture Gallery -- Chapter 18. The Unanswered Question:  Some Remarks on Tagore’s Late Style.
Keywords: Philosophy, Asian; Cultural studies; Philology; Linguistics; Non-Western Philosophy; Cultural Studies; Language and Literature